PERANAN SEKTOR PERTANIAN DALAM PENYERAPAN TENAGA KERJA DI PROVINSI SULAWESI UTARA - Angel ., Warouw; O. Esry H. Laoh; Gene H. M Kapantow (Sam Ratulangi University, 2018)
This study aims to determine the role of agricultural sector in the absorption of labor in North Sulawesi Province. This research was conducted for three months, starting from October until December 2017 in North Sulawesi Province. In this study the data used are secondary data obtained from the Central Bureau of Statistics (BPS) of North Sulawesi Province. The data is processed using the formula Location Quotient (LQ) and Labor Multiplier (Multiplier Shortrun). The results showed that agricultural sector is the most important sector in the absorption of labor in the Province of North Sulawesi. The contribution of agriculture sector on labor absorption period 2009-2016 as much as 39%. The contribution of the agricultural sector in absorbing labor in the Province of North Sulawesi tends to be the same as the contribution of the agricultural sector at the National level.*oehl*.